2014
DOI: 10.1149/2.096404jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Doped Yttrium Chromites as Electrodes for Solid Oxide Fuel Cell by Impedance Method

Abstract: Redox-stable ceramic electrodes, Co and Ni doped yttrium chromites, for solid oxide fuel cell (SOFC) are characterized by electrochemical impedance spectroscopy (EIS) in various P O2 and P H2 atmosphere. The polarization resistances for Y 0.8 Ca 0.2 Cr 0.8 Co 0.2 O 3-δ (YCCC) and Y 0.8 Ca 0.2 Cr 0.9 Ni 0.1 O 3-δ (YCCN) on yttrium stabilized zirconia (YSZ) electrolyte are 0.96 and 8.4 cm 2 in wet H 2 , 1.2 and 36.7 cm 2 in air at 850 • C, respectively. For the anode application, the rate-limiting steps (RDS) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Those results are consistent with the ones reported by Aguadero et al 24 According to the fitting results, the small capacitances and the large characteristic frequencies for the HF arcs of Sr30 and Sr40 indicate that those arcs can be reasonably associated to a charge transfer process. [34][35][36] The incorporation of oxygen into cathode lattice has been taken into account in the ALS element. Meanwhile, the electron transfer from current collector to the cathode must not be the case because Sr30 and Sr40 possess higher electrical conductivities than LNO.…”
Section: Resultsmentioning
confidence: 99%
“…Those results are consistent with the ones reported by Aguadero et al 24 According to the fitting results, the small capacitances and the large characteristic frequencies for the HF arcs of Sr30 and Sr40 indicate that those arcs can be reasonably associated to a charge transfer process. [34][35][36] The incorporation of oxygen into cathode lattice has been taken into account in the ALS element. Meanwhile, the electron transfer from current collector to the cathode must not be the case because Sr30 and Sr40 possess higher electrical conductivities than LNO.…”
Section: Resultsmentioning
confidence: 99%
“…Two kinds of anodes are widely used in the solid oxide fuel cells (SOFCs), including the cermet anodes (e.g., Ni–yttrium-stabilized zirconia (YSZ)) and all-ceramic anodes such as perovskite structure oxides. The steam is commonly supplied together with H 2 fuel to the Ni/YSZ anodes in the SOFCs, demonstrating apparent improvement of their electrochemical performance in humidified H 2 compared to that in dry H 2 . Two categories of mechanisms have been proposed to elucidate the underlying insights into the enhanced hydrogen oxidation reaction (HOR) kinetics under the H 2 flow with steam. On the one hand, Bessler et al reported that the activating effect of water on the HOR kinetics can be only ascribed to equilibrium-potential effect at the Ni/YSZ anodes, without the necessity of assuming additional kinetic or catalytic effect .…”
Section: Introductionmentioning
confidence: 99%
“…Sr-doped LaMnO 3 (LSM) is one of the most studied perovskite materials for solid oxide fuel cell (SOFC) cathodes because of its high electronic conductivity, good oxygen reduction kinetics, and thermal and chemical stability with yttria-stabilized zirconia. For the same reasons, LSM has also been applied in composite electrodes in solid oxide electrolyser cells and catalytic layers and/or electronically conducting phases for mixed conducting membranes and catalytic membrane reactors . At intermediate temperatures (600–800 °C), the main limiting factor for the performance of SOFCs has been ascribed to the oxygen reduction reaction (ORR) at the cathode. , Oxygen surface exchange and surface diffusion of oxide ions have been identified as two key processes that control the ORR . Surface exchange kinetics remains an elusive property because it involves several steps including adsorption and dissociation of molecular oxygen, reduction (charge transfer), and incorporation of oxygen species into the cathode or electrolyte.…”
Section: Introductionmentioning
confidence: 99%